Morphing as a Selection Tool in the Rhinoplasty Consult: A Cross-Sectional Study - Lekakis, Garyfalia; Sykes, Jonathan; Hens, Greet; Hellings, Peter William (Facial Plastic Surgery, 2020)
Despite the recognized value of morphing in the literature, this preoperative tool has never been studied in the context of selection process in rhinoplasty. The main purpose of this article is to identify the use of morphing as a filter for unsuitable patients, the attrition rate from the initial consultation to surgery, and whether patients' appreciation on morphing influence their decision-making process. Three-hundred thirty-four consecutive patients, seeking rhinoplasty, underwent two-dimensional computer imaging and completed a 14-question survey about their opinion on morphing. Based on the presence or absence of patient/physician consensus on the expected outcomes during simulation, patients were divided into accepted or rejected candidates for surgery. Accepted candidates were scheduled for rhinoplasty and subdivided into those who underwent surgery, those who postponed their surgery (static), and those who cancelled their procedure. Their responses to the survey were compared between different patients' categories. Forty-four patients (13.2%) were rejected for rhinoplasty since consensus was not achieved during morphing. From 290 accepted patients, 178 underwent their operation (53.3%), 74 patients (22.1%) postponed their rhinoplasty, and 38 (11.4%) cancelled their surgery. Fifty-seven percent of rejected patients and 42% of the static group were not satisfied with the proposed results of morphing, in contrast with 16% of the operated group. Sixty-four percent of rejected patients, and 47% of the static group were not reassured after morphing, compared with 26% of the operated group. Presence or absence of consensus during morphing can guide the surgeon regarding a given patients' suitability for surgery. Patient satisfaction and reassurance with the morphed images can be a good predictor of patients who will proceed to surgery, calling attention to the value of morphing as a selection tool for surgeons and patients alike.
Keywords: computer imaging; morphing; patient selection; rhinoplasty consult; computer simulation